Radioligand binding studies of alpha 1-adrenoceptor subtypes in rat heart. - Michel, M. C. (1994)
1. In order to characterize the alpha 1-adrenoceptor subtypes mediating positive inotropic effects of adrenaline (in the presence of propranolol) in rat right ventricular strips and the Ca2+ sources used to elicit them, we have used radioligand binding to identify the alpha 1-adrenoceptor subtypes present in rat heart and the alpha 1-adrenoceptor affinity and subtype-selectivity of various pharmacological tools. 2. Amitryptiline, mianserin, trimipramine, oxaprotiline, clonidine, chloroethylclonidine, phenoxybenzamine, BE 2254 and 8-OH-DPAT competed for [3H]-prazosin binding in rat heart, vas deferens, liver, spleen, cerebral cortex and hippocampus but none of them displayed detectable alpha 1-adrenoceptor subtype-selectivity; nitrendipine did not compete for [3H]-prazosin binding in concentrations up to 5 mumol 1(-1). 3. The alpha 1 A-adrenoceptor-selective, 5-methyl-urapidil, (+)-niguldipine, and to a lesser extent (-)-niguldipine competed for [3H]-prazosin binding in rat heart, vas deferens, cerebral cortex and hippocampus with shallow and biphasic curves; analysis of these curves demonstrated that rat heart contains alpha 1A-and alpha 1B-adrenoceptors in a 20:80 ratio. 4. Treatment of rat right ventricular strips with 100 mumol l-1 chloroethylclonidine for 30 min at 30 degrees C followed by 60 min washout reduced the number of alpha 1-adrenoceptors, as assessed by [3H]-prazosin saturation experiments, by 74%. Treatment with 100 mumol l(-1) CdCl2 did not affect number or affinity of cardiac alpha 1-adrenoceptors and combined treatment with chlorethylclonidine and CdCl2 reduced alpha 1-adrenoceptor number by 90%.(ABSTRACT TRUNCATED AT 250 WORDS)